Role of The WTO (World Trade Organization) To Limit Dumping Practice - Kondang Pribadi, Adhimaz; Gautama, Tirta (Devotion : Journal of Research and Community Service, 2023)
International trade is a cross-border buying and selling transaction, which involves two parties and crosses state boundaries. Dumping is a system of selling goods on foreign markets in large quantities at very low prices with the aim that domestic purchase prices are not lowered so that they can eventually dominate foreign markets and regain control of prices. From the above background, the problem in this research is the role of the WTO (World Trade Organization) to limit dumping practices. Answering these problems the researchers used a normative juridical approach. Normative juridical approach is an approach that is based on the main legal material by examining theories, concepts, legal principles and laws and regulations related to this research. The results of the study show that in GATT it is clear that the position of dumping is an act of unfair trade (unfair trade practice) because it violates the principles of MFN. This is why he considers dumping as Unfair Trade Practice in GATT. Then the anti-dumping regulation in Article VI of the GATT is intended as a policy to overcome dumping. The WTO in this position is as a forum for dispute resolution and provides a conciliation mechanism to resolve trade disputes that arise. So that the position of the WTO is as a facilitator in preventing dumping disputes.